An Evaluation of the Efficacy of GraphoGame Rime for Promoting English Phonics Knowledge in Poor Readers - Ahmed, Henna; Wilson, Angela; Mead, Natasha; Noble, Hannah; Richardson, Ulla; Wolpert, Mary A.; Goswami, Usha (Frontiers in Education, 2020)
Here we report further analysis of data drawn from a Randomized Controlled Trial (RCT) run in the United Kingdom designed to evaluate the efficacy of an adaptive software game to aid the learning of English phonics, GraphoGame Rime. We evaluate the efficacy of GraphoGame Rime for the “top half” of players in the RCT, children aged 6 to 7 years who played above the group mean play progress point (95 children). We also analyse 3 sub-groupings of this cohort. The GraphoGame family of games in different languages was originally designed to support children at family risk of dyslexia, hence we analysed data for the subgroup of the GraphoGame Rime children who were struggling in school and had Individual Education Plans (IEPs). Secondly, we analysed data from the younger children in the RCT, born in the Spring and Summer months, as international studies of GraphoGame have found the strongest effects during the first year of reading tuitionand our participants were in their second year of reading tuition. Finally, we analysed GraphoGame Rime data from players in schools rated as “requiring improvement”. Schools that are found to be “requiring improvement” in the United Kingdom are encouraged to use additional teaching strategies to achieve better outcomes. GraphoGame Rime is relatively cheap to acquire and easy to implement, hence if it offers significant gains over “business-as-usual” this would be a valulable additional strategy for such schools. We find that GraphoGame Rime is more effective than “business-as-usual” in developing knowledge of English phonics for all of the groupings analysed. We conclude that the supplementary use of GraphoGame Rime in addition to ongoing classroom literacy instruction can benefit children in learning phonic decoding and spelling skills.